(untitled) (Al-Qamar, 2022)
There has been a difference of opinion among the jurists regarding the Shariah ruling of the currency notes. The reason that led to this difference was the lack of elaborations in classical fiqh, as at that time the only prevailing currencies were gold and silver. Metal coins namely fuloos were also available but their usage was limited to only those transactions that involved low-priced goods. The status of currency notes remained controversial in the past until eventually the contemporary scholars accepted currency notes as gold and silver while applying the shariah rulings of Riba and Bai’ Sarf on them. Contrarily, numerous scholars from the Indo-Pak subcontinent have rejected the idea of applying the rulings of Riba and Bai’ Sarf on Currency Notes on the basis of the Hanafi school’s elaborated effective cause of Riba (Illat-e-Riba). The reason for this difference of opinion is the variety of viewpoints available among scholars regarding the effective cause of Riba. In the current literature, the majority of the research is carried out regarding the juristic nature and other aspects of this issue. However, in this paper, we discuss the actual cause of the controversiality in the effective cause of Riba and its impact on the currency note.